The Influence of Influencer Marketing and Brand Awareness on Purchase Decisions of Chatime in Bengkulu City - Aisyah Arista Wahyuni; Arifah Hidayati; Syofian Syofian (Journal of Research in Social Science and Humanities, 2024)
This study aims to analyze the influence of influencer marketing on purchase decisions, the influence of brand awareness on purchase decisions, and the influence of both influencer marketing and brand awareness on purchase decisions. The population of this study is Generation Z who purchase Chatime in Bengkulu City. The sample consists of 100 respondents, selected through purposive sampling and non-probability sampling using the Cochran formula. Data analysis was performed using multiple regression and hypothesis testing, employing SPSS version 25. The results of this study conclude that (1) influencer marketing has a positive influence on purchase decisions with a significance of 0.018 0.05, (2) brand awareness has a positive influence on purchase decisions with a significance of 0.000 0.05, and (3) influencer marketing and brand awareness simultaneously have a positive influence with a significance of 0.000 0.05.